Morphology and strength differences between elite C1 and K1 canoe slalom competitors - Busta, J. (VIII Congreso Internacional De Entrenadores De Piragüismo en Aguas Tranquilas, 2022)
Introduction: Anthropometric and strength parameters are important factors of the white water slalom performance. However, differences between kayak (K1) and canoe (C1) category are still unknown. The aim of this study is to identify if morphology and strength differences existed between kayak and canoe paddlers.